Estrategias para la prevención y tratamiento de delitos sexuales en el ámbito educativo - Cuyo Chugchilan, Mariana De Jesús (2017)
This research was carried out with the full support of the educational community, with children, parents and the general community to achieve the strategies and treatment awareness of sexual offenses in adolescents and thus promote the practice human values that today are disappearing as a result of the advancement of technology and social coexistence; this awareness process would take place through talks conferences, projection of educational videos with their respective analysis for on the basis of the same establish their conclusions and recommendations, thus achieving positive results to this problem that influences academic performance and behavior of students, because once the diagnosis made in the school to develop the project we have seen that if there problems of sexual crimes that should be treated promptly with qualified personnel the same as utilize adequate treatment strategies, monitoring and welfare people who commit this type of behavior; so if we can achieve through the implementation of this project is the awareness to people who do not commit such crimes inculcating in them norms of respect, habits of behavior in the society we live achieving encourage youth practice reaching values and good living of the general public....